Network-layer reservation TDM for ad-hoc 802.11 networks - Duff, Kevin Craig (Rhodes University, Faculty of Science, Department of Computer Science, 2008)
Ad-Hoc mesh networks offer great promise. Low-cost ad-hoc mesh networks can be built using popular IEEE 802.11 equipment, but such networks are unable to guarantee each node a fair share of bandwidth. Furthermore, hidden node problems cause collisions which can cripple the throughput of a network. This research proposes a novel mechanism which is able to overcome hidden node problems and provide fair bandwidth sharing among nodes on ad-hoc 802.11 networks, and can be implemented on existing network devices. The scheme uses TDM (time division multiplexing) with slot reservation. A distributed beacon packet latency measurement mechanism is used to achieve node synchronisation. The distributed nature of the mechanism makes it applicable to ad-hoc 802.11 networks, which can either grow or fragment dynamically.
Keywords: Computer networks -- Access control; Computers -- Access control; Computer networks -- Management; Time division multiple access; Ad hoc networks (Computer networks)